Meteorological observations at Syowa Station, Antarctica, 2011 by the 52nd Japanese Antarctic Research Expedition - Junji Hisamitsu; Hideyuki Oguri; Matsumi Takano; Nobumasa Sugiyama; Atsushi Yamamoto (National Institute of Polar Research, 2016)
This report describes the results of meteorological observations at Syowa Station from February 1, 2011 to January 31, 2012, carried out by the Meteorological Observation Team of the 52nd Japanese Antarctic Research Expedition (JARE-52). The observation methods, instruments and statistical methods used by JARE-52 were almost the same as those used by the JARE-51. Remarkable weather phenomena observed during the period of JARE-52 are as follows: 1)JARE-52 experienced heavy snowfall with record-breaking maximum snow depth of the month from February 2011 to May 2011 as well as from December 2011 to January 2012. From June to November 2011, it placed the second in the past record of each month. Total amount of daily snow depth also hit the record high for half of the months during the wintering period. 2)The number of occurrences of the blizzard was 30 times, which was slightly larger than average year. But blizzard occurred every month during winter period. 3)The amount of total ozone over Syowa Station from mid-August to mid-December was continuously less than 220 m atm-cm used as a target for the ozone hole for most of this period. The value for September 21 was 149 m atm-cm, which marked the minimum value of year 2011.